2020
DOI: 10.1038/s41929-020-0472-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural modulation and direct measurement of subnanometric bimetallic PtSn clusters confined in zeolites

Abstract: Modulating the structures of subnanometric metal clusters at the atomic level is a great synthetic and characterization challenge in catalysis. Here we show how the catalytic properties of subnanometric Pt clusters (0.5-0.6 nm) confined in the sinusoidal 10R channels of purely siliceous MFI zeolite modulate upon introduction of partially reduced Sn species that interact with the noble metal at the metal/support interface. The low mobility of Sn in H2 over an extended period of time (>6 h) even at high temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
241
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(256 citation statements)
references
References 56 publications
11
241
0
4
Order By: Relevance
“…Unfortunately, bifunctional zeolite-supported noble metals also have several disadvantages. The metal aggregation on the carrier surface during the high-temperature oxidation–reduction and limited mass transport of guest molecules inside the micropores significantly decrease their catalytic activity and cause fast catalyst deactivation, especially in the case of bulky oxygenated compounds [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, bifunctional zeolite-supported noble metals also have several disadvantages. The metal aggregation on the carrier surface during the high-temperature oxidation–reduction and limited mass transport of guest molecules inside the micropores significantly decrease their catalytic activity and cause fast catalyst deactivation, especially in the case of bulky oxygenated compounds [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spatially confining metal atoms inside the molecular‐scale cavities can effectively prevent their migration and has been considered one of the most straightforward synthetic methods for MACs. The spatial confinement can be realized with the aid of porous materials (i.e., zeolites, [ 21,22 ] metal–organic frameworks (MOFs), [ 23 ] covalent‐organic frameworks (COFs), [ 24 ] and nanostructured carbon [ 25 ] ) or within specific crystal structures. [ 26,27 ] Such delicate nanoscale structures can effectively confine the clusters, ensuring the formation of monodispersed MACs with high uniformity.…”
Section: Synthesis Of Macsmentioning
confidence: 99%
“…Corma and coworkers studied the confinement of Sndecorated Pt clusters within the channels of purely siliceous MFI zeolite for the ODHP. 141 It was suggested that the formation of subnanometric PtSn clusters (0.5-0.6 nm) in terms of their interaction by selective location in the sinusoidal 10R channels of MFI zeolite as shown in Figure 7A was the key to achieve propane conversion of $20% and propylene selectivity of >97%, which had negligible decreases after 70 hours stability test. Hermans and coworkers found that hexagonal boron nitride and boron nitride nanotubes also exhibited high catalytic performances of 14% propane conversion, 79% propene and 12% ethylene selectivity, in which the O-terminated armchair boron nitride edges were suggested as the main catalytic active sites.…”
Section: Oxidative Dehydrogenation Of Propanementioning
confidence: 98%
“…Reproduced with permission: Copyright 2020, Springer Nature. 141 B, Structural representation of the metal-organic framework (MOF) support, NU-1000, as well as the two preparation methods of Co-based catalysts for propane oxidative dehydrogenation of ethane (ODH) catalysis. Reproduced with permission: Copyright 2017, American Chemical Society 145 of promoter ions including Ni(II), Zn(II), Al(III), Ti(IV) and Mo(VI), were selected to decorate the NU-1000 followed by Co(II) ion deposition to prepare the bimetallic-oxo, hydroxo, aqua clusters.…”
Section: Oxidative Dehydrogenation Of Propanementioning
confidence: 99%